1988
DOI: 10.1161/01.cir.77.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with diastolic hypertension and isolated systolic hypertension among men screened for the Multiple Risk Factor Intervention Trial.

Abstract: The large cohort of white men (317,871) In the elderly, pure isolated systolic hypertension (ISH) is associated with increased risks of morbidity and mortality, including a risk of stroke,5-7 but few studies have evaluated pure ISH in individuals less than 60 years of age. The 361,662 men screened for MRFIT offered the opportunity to measure subsequent mortality with respect to the presence of ISH in a relatively young population.Mean arterial pressure (MAP) has also been studied as a risk factor for CHD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
1
10

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(118 citation statements)
references
References 37 publications
7
100
1
10
Order By: Relevance
“…3 These data support actuarial statistics 4 -6 and classic experimental studies based on measurement of systolic pressure 7 and call into question the preoccupation of clinicians, until quite recently, with diastolic pressure exclusively in the definition and management of hypertension.…”
mentioning
confidence: 72%
“…3 These data support actuarial statistics 4 -6 and classic experimental studies based on measurement of systolic pressure 7 and call into question the preoccupation of clinicians, until quite recently, with diastolic pressure exclusively in the definition and management of hypertension.…”
mentioning
confidence: 72%
“…30 In the Multiple Risk Factor Intervention Trial (MRFIT) about 40% of strokes were attributable to elevation of systolic blood pressure above 140 mm Hg. 31 A 10-year longitudinal survey demonstrated that the association between systolic blood pressure and the incidence of strokes persisted at highly advanced ages. 32 On the whole, it has been consistently demonstrated for three decades that isolated systolic hypertension is the greatest risk factor for cerebrovascular complications other than age.…”
Section: Mortalitymentioning
confidence: 99%
“…2,4,[6][7][8] In addition, these studies have clearly demonstrated that SBP is an important and independent cardiovascular risk factor. 2,6,9 In patients with ISH mean arterial pressure (MAP) and vascular resistance may be normal or slightly elevated, while pulse pressure, the difference between SBP and DBP, is increased. [10][11][12] It has been shown that an increase in pulse pressure contributes considerably to the increase in cardiovascular morbidity and mortality seen at higher ages.…”
Section: Introductionmentioning
confidence: 99%